From union clout to corporate couture: Unveiling the impact of trade unions on corporate social responsibility - Anshul Mandliya; Jatin Pandey; Shrihari Suresh Sohani; Rayees Ahmad Sheikh (PLoS ONE, 2025)
Trade unions and corporate social responsibility (CSR) are important institutional mechanisms through which corporations undertake responsibility for their for-profit as well as not-for-profit actions. This study explores the roles of trade unions, management, and shareholders in influencing environmental, social, and governance (ESG) controversies and CSR reporting. Drawing on instrumental stakeholder theory, we argue that while management and shareholders typically focus on governance, profitability, and operational efficiency, trade unions act as critical relational stakeholders advocating for employee welfare and social sustainability. Using a sample of 416 firms over a period of 10 years, our findings reveal that trade unions significantly reduce ESG controversies and enhance CSR reporting by advocating for employee welfare and social sustainability. In contrast, management significantly impacts CSR reporting but notably does not influence ESG controversies. Lastly, shareholders, who are important for governance and profitability, exhibit minimal impact on both ESG controversies and CSR reporting.